Photoelectron emission from solid Ne tested by impurity adsorption - Dmitriev, Yu.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Electron emission was obtained from a solid Ne sample growing from the gas phase on a low temperature substrate. The surface of the sample was irradiated by the light of an open-source microwave discharge running in the gaseous Ne. A second gas flow of CH4 was, simultaneously, passed onto the substrate avoiding the discharge zone. Free electrons ejected into a vacuum chamber during the sample growth were detected by means of the electron cyclotron resonance (ECR) technique. The electron yield was found to be decreaseat increasing CH4 flow. Fitting curves to the experimental data showed that the surface CH4 impurities played the major role in emission quenching. Atemperature effect was observed in which a 4.2 K sample was much more sensitive to CH4 doping than a 1.6 K one. Based on the experimental results, a model was proposed of the surface sites where electrons escape the solid.